Improving logistics scheduling and operations to support offshore wind construction phase - Sylvain Chartron (Logistics Research, 2019)
The increasing construction of offshore wind farms and the expected improved profitability call for a better efficiency in offshore logistics. The purpose of this study is to propose scheduling and operations improvements for logistics to support offshore wind construction. The study conducts a literature review of scientific studies on the offshore wind logistics. Based on this review, a definition of offshore wind logistics during construction phase is proposed. It can be seen that only a few studies have focused on offshore wind logistics (except installation vessel) during wind turbine construction phase. To help closing this gap, a model is proposed to evaluate and select offshore logistics spread in order to support construction phase. Results on simulations show that logistics spread efficiency varies depending on the season, distance to shore and geographical location. Adaptation and combination of logistics concepts may be necessary to achieve best cost efficiency. The results are important as a basis for further empirical studies in this area. At the end, we propose research areas for operational improvements.
Keywords: 650; offshore wind construction; offshore logistics; efficiency; cost optimization model